Sustainable community-based tourism among the indigenous people of Lambir, Sarawak, Malaysia - Lamat, Ripin (2021)
The main purpose of this study is to holistically understand the sustainability of tourism in Lambir through Community Based Tourism (CBT) initiatives. A lack of solid academic studies on the community resources and community development factors created a vast literature gap in this study. A quantitative approach is used in this study to gather and analyse data. Results found that all community resources and community development variables except participation are the predictors of sustainable CBT tourism in rural areas of Lambir. As for community resources (cultural resources, human resources, infrastructure resources, natural resources and financial resources), the cultural resource variable is found to be the most influential variable while in community development (capacity building, entrepreneurship skills and empowerment), capacity building, and entrepreneurship skills are found be stronger predictors of sustainable tourism in rural areas of Lambir. Overall, the cultural resource is the most influential variable among others. However, the impact is not so high of all variables. Moreover, it is essential to invest more in the long term for successful CBT implementation, but it is equally important to focus on community capacity through education and equal opportunity. Thus, the entrepreneurship and capacity building of the community plays a significant role. It is suggested that the community should be given authority in the decision-making process. Apart from that, they must be empowered and financially supported to run their own tourism business. Empowerment is also selected as one of the predictors of sustainable tourism, which implies the community is ready to be self-reliant if given an opportunity without entirely relying on outsiders. Therefore, government organizations need to concentrate more on these areas (significant variables) and support the local community to attain a holistic, sustainable tourism practice. The study is committed to delivering a comprehensive understanding of elusive yet frequently taken for granted predictors which might offer insights into the existing sustainability challenges being faced in rural tourism areas of Malaysia. This study shall also pay critical attention to acknowledging the dissonance of voices from researchers in industries. These public and private organizations have an impact on sustainable community-based tourism development. Particularly, the results of this study have two implications that have arisen from its significant contribution. These contributions are related to theoretical and practical aspects.